1998
DOI: 10.3758/bf03201178
|View full text |Cite
|
Sign up to set email alerts
|

Sources of sentence constraint on lexical ambiguity resolution

Abstract: Results from a series of naming experiments demonstrated that major lexical categories of simple sentences can provide sources of constraint on the interpretation of ambiguous words (homonyms). Manipulation of verb (Experiment 1) or subject noun (Experiment 2) specificity produced contexts that were empirically rated as being strongly biased or ambiguous. Priming was demonstrated for target words related to both senses of a homonym following ambiguous sentences, but only contextually appropriate target words w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
57
0
6

Year Published

2001
2001
2018
2018

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 78 publications
(67 citation statements)
references
References 50 publications
4
57
0
6
Order By: Relevance
“…This is not a pattern predicted by any extant model of lexical ambiguity resolution, since models that incorporate context sensitivity generally assume that context-based selection will reduce, rather than enhance, activation of the alternative meaning (e.g., Swinney and Hakes, 1976;Vu et al, 1998). However, the pattern is consistent with the predictions of the coarse coding hypothesis (Beeman et al, 1994;Jung-Beeman, 2005), which postulates that meaning activation in the RH is diffuse, and thus more likely to encompass multiple, disparate senses of an ambiguous word.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is not a pattern predicted by any extant model of lexical ambiguity resolution, since models that incorporate context sensitivity generally assume that context-based selection will reduce, rather than enhance, activation of the alternative meaning (e.g., Swinney and Hakes, 1976;Vu et al, 1998). However, the pattern is consistent with the predictions of the coarse coding hypothesis (Beeman et al, 1994;Jung-Beeman, 2005), which postulates that meaning activation in the RH is diffuse, and thus more likely to encompass multiple, disparate senses of an ambiguous word.…”
Section: Discussionmentioning
confidence: 95%
“…1981; Swinney and Hakes, 1976;Tabossi, 1988;Vu et al, 1998) have presented homonyms in a biasing context in order to explore the possible effects of non-lexical sources of information on lexical access (e.g., the semantic context in a sentence like "The office walls were so thin that they could hear the ring …"; Onifer & Swinney, 1981). Several classes of models have developed out of this research: exhaustive models (Swinney, 1979), which argue that multiple meanings of an ambiguous word are automatically activated; selective models (Swinney & Hakes, 1976), which suggest that only the contextually-consistent meaning is initially activated; and hybrid models, which argue that context interacts with meaning frequency (e.g., Duffy et al, 1988;Tabossi, 1988).…”
mentioning
confidence: 99%
“…In contrast, Simpson and Krueger (1991) have demonstrated that a strongly biased context could lead to the activation of only the contextually appropriate meaning of an ambiguous word. Finally, Kellas and colleagues (e.g., Martin, Vu, Kellas, & Metcalf, 1999;Vu, Kellas, Metcalf, & Herman, 2000;Vu, Kellas, & Paul, 1998) have established that ambiguity resolution depends on a complex interaction among meaning frequency, context type, and strength of the biased context. Critically, it was found that although meaning frequency does play an important role, its effect can be eliminated, depending on context strength.…”
Section: Situation-based Knowledge and The Resolution Of Lexical Ambimentioning
confidence: 99%
“…3 Perhaps a more productive approach is to identify the factors that will influence the resolution of lexical ambiguity. In addition to the factors of meaning frequency, type of context, and strength of context, Vu et al (1998) have found that the lexical entries in a simple subject-verb-object sentence can provide unique sources of constraint on ambiguity resolution. For example, 2a.…”
Section: Situation-based Knowledge and The Resolution Of Lexical Ambimentioning
confidence: 99%
See 1 more Smart Citation